Dedifferentiated liposarcoma of the oral floor: A case study and literature review of 50 cases of head and neck neoplasm - Nimura, Fumikazu (Oncol Lett, 2018)
Dedifferentiated liposarcoma (DDLS) has a relatively poor prognosis, however this neoplasm rarely occurs in the head and neck. To date, no definite protocol has been established for the diagnosis and treatment of head and neck DDLS. The present study reports the case of a 69-year-old male patient with DDLS of the oral floor. To the best of our knowledge, this is the first documented case of oral floor DDLS. In addition, this is the first reported case with the development of a second primary malignancy following the treatment of head and neck DDLS. A literature review of 50 cases of head and neck DDLS revealed that preoperative biopsy is not reliable for the diagnosis of these tumors and an accurate pathological diagnosis with total resection is preferred.